DETERMINING THE ARMHOLE AND SLEEVE FIT OF MEN'S JACKET - Manzura Sodiqovna Abdurakhimova; Mahsudov Shohruxmirzo Abdulhamid ogli (Modern American Journals, 2025)
This article discusses the stages of controlling the armhole and sleeve setting in men’s jackets, emphasizing the importance of sleeve alignment with body structure, comfort, and design appearance. It highlights the use of control marks (notches) to ensure proper connection between the sleeve and the armhole, the distribution of ease percentages when attaching the sleeve to the armhole, as well as different allowances and adjustments for various construction cuts. The paper also provides information on the adaptation norms for different types of materials.
Keywords: Jacket, construction, armhole, sleeve, misfit, movement discomfort, shape, quality determination, armhole line, arms at joint boundaries, elliptical form, closed width, ease, wearing comfort.